Post-COVID-19 pandemic changes in pertussis incidence among patients with acute respiratory tract infections in Zhejiang, China - Wang, Huabin; Fu, Miao; Chen, Wei; Ma, Yongjun (Frontiers in Microbiology, 2024)
Background: Previous studies have compared the incidence of pertussis before and during the COVID-19 pandemic, finding that public health measures related to COVID-19 contributed to a temporary decline in reported pertussis cases during the pandemic. However, the post-pandemic period has seen a resurgence in respiratory infections, influenced by relaxed health measures and decreased public vigilance. This study investigates the epidemiological dynamics of pertussis among patients with acute respiratory tract infections (ARTI) in Zhejiang Province, China, providing essential reference information for ongoing public health strategies.Methods: This study analyzed multicenter data from January 2023 to May 2024, involving 8,560 patients with ARTI from three hospitals in Zhejiang Province.Inclusion criteria included patients who presented with cough symptoms and were clinically diagnosed with either acute upper respiratory tract infections (URTI) or acute lower respiratory tract infections (LRTI), and who had undergone at least one Bordetella pertussis DNA test. The study analyzed the epidemiological changes of pertussis positivity rates and their associations with time, age, gender, and diagnosis types (URTI and LRTI).Results: From January 2023 to May 2024, the positivity rate and testing number for pertussis among patients with ARTI generally showed a gradual increasing pattern. In March 2024, the positivity rate reached its peak at 31.58%, followed by a weekly decline. The overall positivity rate was 23.59%, with no significant differences observed between genders. Pertussis incidence was higher in patients with LRTI (24.49%) compared to those with URTI (18.63%, OR=1.40, 95% CI: 1.20-1.63, P<0.001) and in outpatients (25.32%) compared to inpatients (6.09%, OR=4.17, 95% CI: 3.07-5.64, P<0.001). According to a generalized additive model analysis, there was a wave-shaped, non-linear relationship between age and pertussis incidence, with a relatively high rate observed in the 5 to 17 age group, peaking at age 10 (33.85%).Additionally, the impact of age, patient type, and diagnosis type on the pertussis infection rate varied across different age groups.After the COVID-19 pandemic, the positivity rate of pertussis in Zhejiang Province peaked in early 2024 and then showed a declining pattern.Children and adolescents were particularly affected, emphasizing the need for enhanced vaccination and public health interventions in this population.